SUPERVISI AKADEMIK KEPALA SEKOLAH - Mutia Rohmawati (Manajer Pendididikan, 2019)
This research investigated 1) Headmaster instructional supervision program, 2) The implementation instructional supervision by head master and 3) The follow up of supervision results by head master. The research method used was qualitative method. The data obtained was analyzed descriptively qualitative. The headmaster of Junior High School 57 Bengkulu Utara has developed a supervisory program in the form of an annual program and supervision schedule. While the semester program supervision was not compiled. The conclusion of the research result was 1) the principal has prepared an annual supervision program consisting of background, legal basis, objectives, scope and schedule of supervision, as outlined in the form of annual program, 2) the principal used classroom visit techniques, teacher board meetings and personal coaching and In house Training. 3) the principal performed follow-up of supervision results in accordance with the found of the planning stages of learning and found in the classroom during supervision.